Observing corporate governance principles: growth strategy for small traders in Zimbabwe - Mugwati, Miriam; Nkala, D. (Midlands State University, 2015)
Illegal activities were rampant throughout the Zimbabwean economy during the economic crisis experienced by the country from the year 2000 to 2008. To ensure their survival, companies were involved in illegal activities which included sourcing for foreign currency from the black market. Under these hardships, some large companies had to stop operation due to the high costs they were incurring. In the absence of large companies, small traders sustained the economy. However, when the economy started to recover the majority of these small traders folded up as they were operating illegally and some of them did not observe corporate governance principles. The paper discusses the reasons for the collapse of many small traders when the economy started to recover by analyzing their conduct in relation to corporate governance principles. The researchers adopt a multiple case study approach to arrive at the reasons for the collapse of some of the small traders. The paper demonstrates that some small traders collapsed when the economy started to recover as a result of the absence of checks and balance systems in the way their businesses were operated, lack of separation of ownership and control on the part of business financiers and absence of a growth strategy.